A glass protective lubricant for high temperature alloys and its preparation method and application
By intercalating polymerization and surface growth of silica in bentonite and combining with other materials, the glass protective lubricant prepared is solved in the prior art erosion and oxidation of protective lubricant in high-temperature alloy processing, and better metal surface protection and forging effects are achieved.
Patent Information
- Application Number
- CN202410531297.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-04-29
AI Technical Summary
In the existing high-temperature alloy processing, protective lubricants are prone to erosion of metals during heating, resulting in surface oxidation and alloy elements depletion, affecting the forging effect and mold life.
By intercalating tannin acid polymerization into bentonite, silica is grown in situ on the surface, and polymerized with silane coupling agent and acrylic monomer, high-alumina borosilicate glass, low-temperature lead-free glass, carboxymethyl cellulose and boron nitride, and a glass protective lubricant obtained by ball milling.
The glass protective lubricant can effectively protect the metal surface at high temperatures, reduce oxidation and alloy element depletion, reduce friction coefficient, extend the service life of the mold, and improve the surface quality of the forgings.
Smart Images

Figure BDA0004818194510000151 
Figure BDA0004818194510000161 
Figure BDA0004818194510000162
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricants, and in particular to a glass protective lubricant for high-temperature alloys, a preparation method and application thereof. Background Art
[0002] At present, in the field of metal profile processing such as alloy steel, since the profile contains S, P, C and other substances to varying degrees, if these trace substances are oxidized, they will directly affect the performance of the metal profile. For example, the special mold steel for aerospace parts is mainly composed of C, Cr, Mo and AI alloy structural steel. During the high-temperature forging process, the precipitation of S, P, C in its organizational structure and metal oxidation have a great impact on the metal properties and forming effect as well as the service life of the mold. Therefore, effective protective measures need to be taken for the processing and forging process of these metal profiles. In the prior art, protective lubricants or other mixtures are mainly used to form a protective coating by coating the surface of the metal profile in multiple layers to achieve protection of the metal during processing and forging, especially high-temperature forging.
[0003] Glass is an ideal lubricant under high-temperature extrusion conditions, and its good lubrication effect has been widely confirmed in stainless steel hot extrusion production at home and abroad. Glass protective lubricant has a certain viscosity and good insulation effect at high temperature. When used during extrusion, it can transform the dry friction of the contact surface into boundary friction as much as possible, thereby improving the surface quality of the product and extending the service life of the tooling. In addition, it reduces the cooling effect of the extrusion tooling on the metal ingot, reduces the friction resistance of the tooling on the metal ingot, reduces the unevenness of metal flow, improves the performance of the extruded product, and reduces the extrusion energy consumption.
[0004] However, the protective lubricants currently used are generally prone to corroding metal blanks during heating, and forming new substances that further damage the metal forming surface and the mold surface. For example, protective lubricants made of silicate glass and borate glass cause serious corrosion to metals during use due to their strong alkalinity, and the corroded parts are extremely difficult to clean. Especially under high temperature conditions such as 1000℃, the corrosion phenomenon of existing protective lubricants is more serious. Summary of the invention
[0005] The purpose of the present invention is to propose a glass protective lubricant for high-temperature alloys and its preparation method and application, which can isolate the surface of the metal material from the air under high temperature and prevent surface oxidation, thereby well protecting the surface of the material, greatly reducing the oxidation and decarburization of stainless steel caused by high temperature during the heating process, preventing the depletion of alloy elements on the surface of the forging, isolating the heat conduction between the forging and the mold, has low corrosiveness, and can effectively improve the surface quality of the forging.
[0006] The technical solution of the present invention is achieved in this way:
[0007] The invention provides a method for preparing a glass protective lubricant for high-temperature alloys. Tannic acid is polymerized and intercalated in bentonite, silicon dioxide is grown in situ on the surface, and after being modified by a silane coupling agent, it is polymerized with acrylic monomers, high-aluminum borosilicate glass, low-temperature lead-free glass, carboxymethyl cellulose and boron nitride are added, and ball milling is performed to obtain the glass protective lubricant for high-temperature alloys.
[0008] As a further improvement of the present invention, the following steps are included:
[0009] S1. Intercalation modification of bentonite: adding calcium-based bentonite to water, adding tannic acid and a catalyst, heating and stirring the reaction, ultrasonic treatment, centrifugation, washing, and drying to obtain intercalation-modified bentonite;
[0010] S2. In situ growth of surface silica: dissolve sodium silicate in water, add the intercalated modified bentonite obtained in step S1, stir and mix evenly, add ethanol, heat and age, add dropwise an aqueous solution of citric acid, continue to keep warm and react, age, and obtain a bentonite / silicon dioxide composite powder;
[0011] S3. Preparation of modified bentonite / silica composite powder: The bentonite / silica composite powder obtained in step S2 is added to ethanol, a composite silane coupling agent is added, the mixture is heated and stirred for reaction, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0012] S4. Preparation of composite glass: mixing high aluminum borosilicate glass and low temperature lead-free glass, and ball milling to obtain composite glass;
[0013] S5. Preparation of glass protective lubricant for high-temperature alloys: sodium acrylate and methyl methacrylate are added into water to prepare a monomer solution, and the modified bentonite / silicon dioxide composite powder obtained in step S3 is added thereto, and the mixture is stirred and mixed evenly, and an initiator is added, and the mixture is heated and stirred to react, and the composite glass, carboxymethyl cellulose and boron nitride obtained in step S4 are added thereto, and the mixture is ball-milled to obtain a glass protective lubricant for high-temperature alloys.
[0014] As a further improvement of the present invention, the mass ratio of the calcium-based bentonite, tannic acid and catalyst in step S1 is 100:12-15:2-4, the catalyst is a Tris-HCl solution with a pH of 8.5-9, the temperature of the heating and stirring reaction is 40-50°C, the time is 2-4h, the power of the ultrasonic treatment is 500-1000W, and the time is 10-20min.
[0015] As a further improvement of the present invention, the mass ratio of sodium silicate, intercalated modified bentonite, ethanol and citric acid in step S2 is 15-20:100:7-10:12-16, the heating aging temperature is 75-85°C, the time is 1-3h, the insulation reaction time is 1-2h, and the aging time is 2-3h.
[0016] As a further improvement of the present invention, the mass ratio of the bentonite / silicon dioxide composite powder and the composite silane coupling agent in step S3 is 100:17-22, the composite silane coupling agent is a mixture of KH570 and KH550, the mass ratio is 15-20:2-4, the temperature of the heating and stirring reaction is 35-45°C, and the time is 1-3h.
[0017] As a further improvement of the present invention, the mass ratio of the high aluminum borosilicate glass to the low temperature lead-free glass in step S4 is 10-15:7-12.
[0018] As a further improvement of the present invention, the mass ratio of sodium acrylate and methyl methacrylate in step S5 is 12-15:10-14, the monomer concentration of the monomer solution is 25-30wt%, the mass ratio of the monomer solution, modified bentonite / silicon dioxide composite powder, initiator, composite glass, carboxymethyl cellulose, and boron nitride is 100:7-10:0.5-1:25-30:3-5:4-6, the ball milling time is 2-4h, the heating and stirring reaction temperature is 55-65°C, and the time is 3-5h.
[0019] Preferably, the initiator is selected from at least one of sodium persulfate, potassium persulfate and ammonium persulfate.
[0020] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0021] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 12-15 parts by weight of tannic acid and 2-4 parts by weight of a catalyst were added, heated to 40-50 ° C, stirred for 2-4 hours, ultrasonically treated at 500-1000W for 10-20 minutes, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0022] The catalyst is a Tris-HCl solution with a pH of 8.5-9;
[0023] S2. In situ growth of surface silica: 15-20 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, and the mixture was stirred and mixed evenly, 7-10 parts by weight of ethanol was added, and the mixture was heated to 75-85°C, aged for 1-3h, and 50 parts by weight of an aqueous solution containing 12-16 parts by weight of citric acid was added dropwise, and the reaction was continued at a temperature of 1-2h, and aged for 2-3h to obtain a bentonite / silicon dioxide composite powder;
[0024] S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 is added to 200 parts by weight of ethanol, 17-22 parts by weight of a composite silane coupling agent is added, heated to 35-45 ° C, stirred for 1-3h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0025] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 15-20:2-4;
[0026] S4. Preparation of composite glass: 10-15 parts by weight of high aluminum borosilicate glass and 7-12 parts by weight of low-temperature lead-free glass were mixed and ball-milled to obtain a composite glass;
[0027] S5. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 25-30wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 12-15:10-14, 7-10 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred and mixed evenly, 0.5-1 parts by weight of an initiator is added, and the mixture is heated to 55-65°C and stirred for reaction for 3-5 hours, 25-30 parts by weight of the composite glass obtained in step S4, 3-5 parts by weight of carboxymethyl cellulose, and 4-6 parts by weight of boron nitride are added, and the mixture is ball-milled for 2-4 hours to obtain a glass protective lubricant for high-temperature alloys.
[0028] The present invention further protects a glass protective lubricant for high-temperature alloys prepared by the above preparation method.
[0029] The present invention further protects the use of the above-mentioned glass protection lubricant for high-temperature alloys in the preparation of stainless steel forging.
[0030] The present invention has the following beneficial effects:
[0031] The bentonite of the present invention is a silicate mineral, which is a laminated structure composed of aluminum oxide layers (octahedron) and silicon dioxide layers (tetrahedron). The interlayers are maintained by weak interactions such as van der Waals forces and electrostatic forces. The interlayer spacing is enlarged by self-polymerization of tannic acid and intercalation in the bentonite, and the surface has abundant active groups such as carboxyl groups and hydroxyl groups.
[0032] Sodium silicate is electrostatically adsorbed on the layered structure, and citric acid is added to make nano silicon dioxide adhere to the intercalated modified bentonite as much as possible, and the bentonite / silicon dioxide composite powder is obtained by reaction, and further modified by a silane coupling agent KH570 with a double bond and a silane coupling agent KH550 with an amino group. On the one hand, the double bond can be polymerized with the acrylic monomer to be uniformly dispersed in the acrylic resin, and on the other hand, the amino group also improves the adhesion and dispersibility to the alloy metal. The modified bentonite / silicon dioxide composite powder obtained by the present invention reduces the corrosion of glass to metal, improves lubricity, reduces the friction coefficient, and improves the high temperature resistance and oxidation protection performance of the lubricant.
[0033] This glass protection lubricant is added with composite glass. High-aluminum borosilicate glass can improve chemical stability and continue high-temperature protection, meeting the protection and lubrication of metal blanks during heating, insulation, and forging in high-temperature sections. Low-temperature lead-free glass can ensure that forgings quickly melt into a film during low-temperature and heating processes, playing a role in isolating harmful gases, softening and melting in low-temperature sections, and achieving lubrication and protection of metal blanks at lower temperatures. Composite glass lubricants can achieve good performance matching and connection when heating and cooling in a wide temperature range, meeting the requirements of the forging process for the continuous temperature change process of blank heating, insulation, deformation, and cooling, maintaining good protection and lubrication effects in the entire forging temperature range, and can have better protection effects.
[0034] In addition, the boron nitride added in the present invention has good high temperature resistance and lubrication performance, can further reduce the friction coefficient, and has good stability to high temperatures. Carboxymethyl cellulose improves the viscosity and suspension of the lubricant, and can improve the balance, suspension effect and coating performance of the slurry.
[0035] The glass protective lubricant of the present invention can isolate the surface of metal materials from the air under high temperature and prevent surface oxidation, thereby well protecting the surface of the material, greatly reducing the oxidation and decarburization of stainless steel caused by high temperature during the heating process, preventing the depletion of alloy elements on the surface of the forging, isolating the heat conduction between the forging and the mold, has low corrosiveness, and can effectively improve the surface quality of the forging.
[0036] The glass protective lubricant of the present invention will gradually soften when heated and turn into a viscous state, with a reduced thickness, increased density, and a sharp decrease in porosity, forming a continuous, dense, and airtight glass film on the metal surface. The glass protective lubricant has good high-temperature viscosity and fluidity, and has certain plasticity and self-healing ability. When the metal undergoes plastic deformation, the glass protective lubricant flows with the metal and withstands the deformation pressure, which can form fluid lubrication friction conditions between the forging and the mold, greatly reduce the friction coefficient, and reduce the friction and wear of the metal. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The high aluminum borosilicate glass is high borosilicate K9 aluminosilicate glass purchased from Dongguan Jingtuo New Glass Technology Co., Ltd. The main components are shown in Table 1.
[0039] Table 1 Glass composition (%, mass fraction)
[0040] <![CDATA[SiO2]]> <![CDATA[B2O3]]> <![CDATA[Na2O]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Al2O3]]> other 49-50 17-18 6-8 1-1.2 1.2-1.3 1.1-1.4 18-19 1.1-6.7
[0041] Low-temperature lead-free glass was purchased from Lingshou County Huashuo Mineral Products Processing Factory, 2000 mesh, and the main components are shown in Table 2.
[0042] Table 2 Glass composition (%, mass fraction)
[0043] <![CDATA[SiO2]]> <![CDATA[B2O3]]> <![CDATA[Na2O]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Al2O3]]> other 65-67 6-7 5-7 2-2.5 1-2 2-3 10-12 0.5-9
[0044] Calcium-based bentonite was purchased from Shijiazhuang Aihong Mineral Products Co., Ltd., and montmorillonite w≥80%.
[0045] Example 1
[0046] This embodiment provides a method for preparing a glass protective lubricant for high-temperature alloys, which specifically includes the following steps:
[0047] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 12 parts by weight of tannic acid and 2 parts by weight of a catalyst were added, heated to 40°C, stirred for 2h, ultrasonically treated at 500W for 10min, centrifuged, washed, and dried to obtain intercalation-modified bentonite;
[0048] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0049] S2. In situ growth of surface silica: 15 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, stirred and mixed for 20 min, 7 parts by weight of ethanol was added, heated to 75 ° C, aged for 1 h, 50 parts by weight of an aqueous solution containing 12 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 1 h, and aged for 2 h to obtain a bentonite / silicon dioxide composite powder;
[0050] S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 was added to 200 parts by weight of ethanol, 17 parts by weight of a composite silane coupling agent was added, heated to 35 ° C, stirred for 1 h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0051] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 15:2;
[0052] S4. Preparation of composite glass: 10 parts by weight of high-aluminum borosilicate glass and 7 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0053] S5. Preparation of a glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 25wt%, wherein the mass ratio of the sodium acrylate to the methyl methacrylate is 12:10; 7 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred and mixed for 15 minutes; 0.5 parts by weight of sodium persulfate are added, and the mixture is heated to 55°C and stirred for reaction for 3 hours; 25 parts by weight of the composite glass obtained in step S4, 3 parts by weight of carboxymethyl cellulose, and 4 parts by weight of boron nitride are added, and the mixture is ball-milled for 2 hours to obtain a glass protective lubricant for high-temperature alloys.
[0054] Example 2
[0055] This embodiment provides a method for preparing a glass protective lubricant for high-temperature alloys, which specifically includes the following steps:
[0056] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 15 parts by weight of tannic acid and 4 parts by weight of a catalyst were added, heated to 50 ° C, stirred for 4 hours, ultrasonically treated at 1000W for 20 minutes, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0057] The catalyst is a Tris-HCl solution with a pH of 9;
[0058] S2. In situ growth of surface silica: 20 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, stirred and mixed for 20 min, 10 parts by weight of ethanol was added, heated to 85 ° C, aged for 3 h, 50 parts by weight of an aqueous solution containing 16 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 2 h, and aged for 3 h to obtain a bentonite / silicon dioxide composite powder;
[0059] S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 was added to 200 parts by weight of ethanol, 22 parts by weight of a composite silane coupling agent was added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0060] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 20:4;
[0061] S4. Preparation of composite glass: 15 parts by weight of high aluminum borosilicate glass and 12 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0062] S5. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 30wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 15:14; 10 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred for 15 minutes; 1 part by weight of potassium persulfate is added, and the mixture is heated to 65°C and stirred for reaction for 5 hours; 30 parts by weight of the composite glass obtained in step S4, 5 parts by weight of carboxymethyl cellulose, and 6 parts by weight of boron nitride are added, and the mixture is ball-milled for 4 hours to obtain a glass protective lubricant for high-temperature alloys.
[0063] Example 3
[0064] This embodiment provides a method for preparing a glass protective lubricant for high-temperature alloys, which specifically includes the following steps:
[0065] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 13 parts by weight of tannic acid and 3 parts by weight of a catalyst were added, heated to 45 ° C, stirred for 3 h, ultrasonically treated at 700 W for 15 min, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0066] The catalyst is a Tris-HCl solution with a pH of 8.7;
[0067] S2. In situ growth of surface silica: 17 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, stirred and mixed for 20 min, 8.5 parts by weight of ethanol was added, heated to 80 ° C, aged for 2 h, 50 parts by weight of an aqueous solution containing 14 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 1.5 h, and aged for 2.5 h to obtain a bentonite / silica composite powder;
[0068] S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 was added to 200 parts by weight of ethanol, 20 parts by weight of a composite silane coupling agent was added, heated to 40 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0069] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 17:3;
[0070] S4. Preparation of composite glass: 12 parts by weight of high-aluminum borosilicate glass and 10 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0071] S5. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 13:12; 8.5 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred for 15 minutes; 0.7 parts by weight of sodium persulfate are added, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the composite glass obtained in step S4, 4 parts by weight of carboxymethyl cellulose, and 5 parts by weight of boron nitride are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0072] Example 4
[0073] Compared with Example 3, the difference is that the composite silane coupling agent is a single KH570.
[0074] Example 5
[0075] Compared with Example 3, the difference is that the composite silane coupling agent is a single KH550.
[0076] Comparative Example 1
[0077] Compared with Example 3, the difference is that step S1 is not performed.
[0078] The details are as follows:
[0079] S1. In situ growth of surface silica: 17 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of calcium bentonite was added, the mixture was stirred for 20 min, 8.5 parts by weight of ethanol was added, the mixture was heated to 80 ° C, aged for 2 h, 50 parts by weight of an aqueous solution containing 14 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 1.5 h, and aged for 2.5 h to obtain a bentonite / silica composite powder;
[0080] S2. Preparation of modified bentonite / silicon dioxide composite powder: 100 parts by weight of the bentonite / silicon dioxide composite powder obtained in step S1 was added to 200 parts by weight of ethanol, 20 parts by weight of a composite silane coupling agent was added, heated to 40°C, stirred for 2h, centrifuged, washed, and dried to obtain a modified bentonite / silicon dioxide composite powder;
[0081] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 17:3;
[0082] S3. Preparation of composite glass: 12 parts by weight of high aluminum borosilicate glass and 10 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0083] S4. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 13:12; 8.5 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S2 are added to 100 parts by weight of the monomer solution, and the mixture is stirred for 15 minutes; 0.7 parts by weight of sodium persulfate are added, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the composite glass obtained in step S3, 4 parts by weight of carboxymethyl cellulose, and 5 parts by weight of boron nitride are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0084] Comparative Example 2
[0085] Compared with Example 3, the difference is that step S2 is not performed.
[0086] The details are as follows:
[0087] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 13 parts by weight of tannic acid and 3 parts by weight of a catalyst were added, heated to 45 ° C, stirred for 3 h, ultrasonically treated at 700 W for 15 min, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0088] The catalyst is a Tris-HCl solution with a pH of 8.7;
[0089] S2. Preparation of modified bentonite powder: 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added to 200 parts by weight of ethanol, 20 parts by weight of a composite silane coupling agent was added, heated to 40 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain a modified bentonite powder;
[0090] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 17:3;
[0091] S3. Preparation of composite glass: 12 parts by weight of high aluminum borosilicate glass and 10 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0092] S4. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 13:12; 8.5 parts by weight of modified bentonite powder obtained in step S2 are added to 100 parts by weight of the monomer solution, and the mixture is stirred for 15 minutes; 0.7 parts by weight of sodium persulfate are added, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the composite glass obtained in step S3, 4 parts by weight of carboxymethyl cellulose, and 5 parts by weight of boron nitride are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0093] Comparative Example 3
[0094] Compared with Example 3, the difference is that step S3 is not performed.
[0095] The details are as follows:
[0096] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 13 parts by weight of tannic acid and 3 parts by weight of a catalyst were added, heated to 45 ° C, stirred for 3 h, ultrasonically treated at 700 W for 15 min, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0097] The catalyst is a Tris-HCl solution with a pH of 8.7;
[0098] S2. In situ growth of surface silica: 17 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, stirred and mixed for 20 min, 8.5 parts by weight of ethanol was added, heated to 80 ° C, aged for 2 h, 50 parts by weight of an aqueous solution containing 14 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 1.5 h, and aged for 2.5 h to obtain a bentonite / silica composite powder;
[0099] S3. Preparation of composite glass: 12 parts by weight of high aluminum borosilicate glass and 10 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0100] S4. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 13:12; 8.5 parts by weight of the bentonite / silicon dioxide composite powder obtained in step S2 are added to 100 parts by weight of the monomer solution, and the mixture is stirred for 15 minutes; 0.7 parts by weight of sodium persulfate are added, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the composite glass obtained in step S3, 4 parts by weight of carboxymethyl cellulose, and 5 parts by weight of boron nitride are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0101] Comparative Example 4
[0102] Compared with Example 3, the difference is that high-aluminum borosilicate glass is not added in step S4.
[0103] The details are as follows:
[0104] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 13 parts by weight of tannic acid and 3 parts by weight of a catalyst were added, heated to 45 ° C, stirred for 3 h, ultrasonically treated at 700 W for 15 min, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0105] The catalyst is a Tris-HCl solution with a pH of 8.7;
[0106] S2. In situ growth of surface silica: 17 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, stirred and mixed for 20 min, 8.5 parts by weight of ethanol was added, heated to 80 ° C, aged for 2 h, 50 parts by weight of an aqueous solution containing 14 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 1.5 h, and aged for 2.5 h to obtain a bentonite / silica composite powder;
[0107] S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 was added to 200 parts by weight of ethanol, 20 parts by weight of a composite silane coupling agent was added, heated to 40 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0108] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 17:3;
[0109] S4. Preparation of glass: low temperature lead-free glass is glass;
[0110] S5. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 13:12; 8.5 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred and mixed for 15 minutes; 0.7 parts by weight of sodium persulfate are added, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the glass obtained in step S4, 4 parts by weight of carboxymethyl cellulose, and 5 parts by weight of boron nitride are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0111] Comparative Example 5
[0112] Compared with Example 3, the difference is that low-temperature lead-free glass is not added in step S4.
[0113] The details are as follows:
[0114] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 13 parts by weight of tannic acid and 3 parts by weight of a catalyst were added, heated to 45 ° C, stirred for 3 h, ultrasonically treated at 700 W for 15 min, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0115] The catalyst is a Tris-HCl solution with a pH of 8.7;
[0116] S2. In situ growth of surface silica: 17 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, stirred and mixed for 20 min, 8.5 parts by weight of ethanol was added, heated to 80 ° C, aged for 2 h, 50 parts by weight of an aqueous solution containing 14 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 1.5 h, and aged for 2.5 h to obtain a bentonite / silica composite powder;
[0117] S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 was added to 200 parts by weight of ethanol, 20 parts by weight of a composite silane coupling agent was added, heated to 40 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0118] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 17:3;
[0119] S4. Preparation of glass: high aluminum borosilicate glass is glass;
[0120] S5. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 13:12; 8.5 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred and mixed for 15 minutes; 0.7 parts by weight of sodium persulfate are added, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the glass obtained in step S4, 4 parts by weight of carboxymethyl cellulose, and 5 parts by weight of boron nitride are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0121] Comparative Example 6
[0122] Compared with Example 3, the difference is that no modified bentonite / silicon dioxide composite powder is added in step S5.
[0123] The details are as follows:
[0124] S1. Preparation of composite glass: 12 parts by weight of high-aluminum borosilicate glass and 10 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0125] S2. Preparation of a glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 13:12; 0.7 parts by weight of sodium persulfate are added to 100 parts by weight of the monomer solution, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the composite glass obtained in step S1, 4 parts by weight of carboxymethyl cellulose, and 13.5 parts by weight of boron nitride are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0126] Comparative Example 7
[0127] Compared with Example 3, the difference is that boron nitride is not added in step S5.
[0128] The details are as follows:
[0129] S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 13 parts by weight of tannic acid and 3 parts by weight of a catalyst were added, heated to 45 ° C, stirred for 3 h, ultrasonically treated at 700 W for 15 min, centrifuged, washed, and dried to obtain intercalation modified bentonite;
[0130] The catalyst is a Tris-HCl solution with a pH of 8.7;
[0131] S2. In situ growth of surface silica: 17 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, stirred and mixed for 20 min, 8.5 parts by weight of ethanol was added, heated to 80 ° C, aged for 2 h, 50 parts by weight of an aqueous solution containing 14 parts by weight of citric acid was added dropwise, the reaction was continued at room temperature for 1.5 h, and aged for 2.5 h to obtain a bentonite / silica composite powder;
[0132] S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 was added to 200 parts by weight of ethanol, 20 parts by weight of a composite silane coupling agent was added, heated to 40 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder;
[0133] The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 17:3;
[0134] S4. Preparation of composite glass: 12 parts by weight of high-aluminum borosilicate glass and 10 parts by weight of low-temperature lead-free glass were mixed and ball-milled for 2h to obtain a composite glass;
[0135] S5. Preparation of a glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 27wt%, wherein the mass ratio of the sodium acrylate to the methyl methacrylate is 13:12; 13.5 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred and mixed for 15 minutes; 0.7 parts by weight of sodium persulfate are added, and the mixture is heated to 60°C and stirred for reaction for 4 hours; 27 parts by weight of the composite glass obtained in step S4 and 4 parts by weight of carboxymethyl cellulose are added, and the mixture is ball-milled for 3 hours to obtain a glass protective lubricant for high-temperature alloys.
[0136] Test Example 1
[0137] The performance of the glass protective lubricants for high-temperature alloys prepared in Examples 1-5 of the present invention and Comparative Examples 1-7 was tested.
[0138] The results are shown in Table 3.
[0139] The American Theta inner cylinder rotation viscometer was used to measure the high temperature viscosity of the glass protective lubricant for high temperature alloys at different temperatures.
[0140] The glass protective lubricant of the high-temperature alloy was made into a cylindrical sample of 3mm×3mm, and its morphological changes were observed during the temperature-opening process using a GX high-temperature physical property tester.
[0141] Table 3
[0142]
[0143]
[0144] It can be seen from the above table that the high-temperature alloy glass protective lubricants prepared in Examples 1-3 of the present invention have good comprehensive properties.
[0145] Test Example 2
[0146] According to "HB7065-1994 Specification for Glass Protective Lubricant for Thermal Deformation of Metal Materials", the high-temperature alloy glass protective lubricants prepared in Examples 1-5 of the present invention and Comparative Examples 1-7 were used to measure the friction coefficient (μ) of the stainless steel surface before and after being coated with the high-temperature alloy glass protective lubricant at different temperatures through a ring upsetting test on a 630t hydraulic press.
[0147] The results are shown in Table 4.
[0148] Table 4
[0149]
[0150]
[0151] It can be seen from the above table that the high-temperature alloy glass protective lubricant prepared in Examples 1-3 of the present invention can well reduce the friction coefficient of the stainless steel surface.
[0152] Test Example 3
[0153] Stainless steel samples coated with and not coated with the high-temperature alloy glass protection lubricant prepared in Examples 1-5 of the present invention and Comparative Examples 1-7 were kept at 1180° C. for 30 min, and the oxide scale thickness and the depth of the affected layer on the metal surface after heating were compared.
[0154] The results are shown in Table 5.
[0155] Table 5
[0156]
[0157]
[0158] It can be seen from the above table that the glass protective lubricant of the high-temperature alloy prepared in Examples 1-3 of the present invention can form a dense, continuous and uniform glass film on the surface of the stainless steel sample after heating, which weakens the penetration and diffusion of atmospheric gas molecules on the surface of the stainless steel sample and plays a protective role. After heating, there is no obvious oxide scale shedding on the surface of the sample; while the surface of the uncoated sample has serious surface oxidation and the oxide scale layer shedding.
[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a glass protective lubricant for high temperature alloys, characterized in that: Tannic acid is polymerized and intercalated in bentonite, silicon dioxide is grown in situ on the surface, and after being modified by a silane coupling agent, it is polymerized with acrylic monomers, high-aluminum borosilicate glass, low-temperature lead-free glass, carboxymethyl cellulose, and boron nitride are added, and ball milling is performed to obtain a glass protective lubricant for high-temperature alloys; The following steps are involved: S1. Intercalation modification of bentonite: adding calcium-based bentonite to water, adding tannic acid and a catalyst, heating and stirring the reaction, ultrasonic treatment, centrifugation, washing, and drying to obtain intercalation-modified bentonite; the mass ratio of the calcium-based bentonite, tannic acid and catalyst is 100:12-15:2-4; S2. In-situ growth of surface silica: dissolve sodium silicate in water, add the intercalation modified bentonite obtained in step S1, stir and mix evenly, add ethanol, heat and age, dropwise add an aqueous solution of citric acid, continue to keep warm for reaction, age, and obtain a bentonite / silicon dioxide composite powder; the mass ratio of the sodium silicate, intercalation modified bentonite, ethanol, and citric acid is 15-20:100:7-10:12-16; S3. Preparation of modified bentonite / silicon dioxide composite powder: adding the bentonite / silicon dioxide composite powder obtained in step S2 to ethanol, adding a composite silane coupling agent, heating and stirring the reaction, centrifuging, washing, and drying to obtain a modified bentonite / silicon dioxide composite powder; the mass ratio of the bentonite / silicon dioxide composite powder to the composite silane coupling agent is 100:17-22, the composite silane coupling agent is a mixture of KH570 and KH550, the mass ratio is 15-20:2-4, the temperature of the heating and stirring reaction is 35-45°C, and the time is 1-3h; S4. Preparation of composite glass: The high aluminum borosilicate glass and the low temperature lead-free glass were mixed and ball-milled to obtain a composite glass; the mass ratio of the high aluminum borosilicate glass and the low temperature lead-free glass was 10-15:7-12; S5. Preparation of glass protective lubricant for high-temperature alloys: add sodium acrylate and methyl methacrylate into water to prepare a monomer solution, add the modified bentonite / silicon dioxide composite powder obtained in step S3, stir and mix evenly, add an initiator, heat and stir to react, add the composite glass, carboxymethyl cellulose and boron nitride obtained in step S4, and ball mill to obtain a glass protective lubricant for high-temperature alloys; the mass ratio of the sodium acrylate and methyl methacrylate is 12-15:10-14, and the mass ratio of the monomer solution, modified bentonite / silicon dioxide composite powder, initiator, composite glass, carboxymethyl cellulose and boron nitride is 100:7-10:0.5-1:25-30:3-5:4-6.
2. The preparation method according to claim 1, characterized in that: In step S1, the catalyst is a Tris-HCl solution with a pH of 8.5-9, the temperature of the heating and stirring reaction is 40-50°C, the time is 2-4 hours, and the power of the ultrasonic treatment is 500-1000W, and the time is 10-20 minutes.
3. The preparation method according to claim 1, characterized in that: The heating and aging temperature in step S2 is 75-85°C, the time is 1-3h, the insulation reaction time is 1-2h, and the aging time is 2-3h.
4. The preparation method according to claim 1, characterized in that: The monomer concentration of the monomer solution in step S5 is 25-30 wt %, the ball milling time is 2-4 h, and the heating and stirring reaction temperature is 55-65° C. for 3-5 h.
5. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Intercalation modification of bentonite: 100 parts by weight of calcium-based bentonite was added to 500 parts by weight of water, 12-15 parts by weight of tannic acid and 2-4 parts by weight of a catalyst were added, heated to 40-50 ° C, stirred for 2-4 hours, ultrasonically treated at 500-1000W for 10-20 minutes, centrifuged, washed, and dried to obtain intercalation modified bentonite; The catalyst is a Tris-HCl solution with a pH of 8.5-9; S2. In situ growth of surface silica: 15-20 parts by weight of sodium silicate was dissolved in 500 parts by weight of water, 100 parts by weight of the intercalated modified bentonite obtained in step S1 was added, and the mixture was stirred and mixed evenly, 7-10 parts by weight of ethanol was added, and the mixture was heated to 75-85°C, aged for 1-3h, and 50 parts by weight of an aqueous solution containing 12-16 parts by weight of citric acid was added dropwise, and the reaction was continued at a temperature of 1-2h, and aged for 2-3h to obtain a bentonite / silicon dioxide composite powder; S3. Preparation of modified bentonite / silica composite powder: 100 parts by weight of the bentonite / silica composite powder obtained in step S2 is added to 200 parts by weight of ethanol, 17-22 parts by weight of a composite silane coupling agent is added, heated to 35-45 ° C, stirred for 1-3h, centrifuged, washed, and dried to obtain a modified bentonite / silica composite powder; The composite silane coupling agent is a mixture of KH570 and KH550, with a mass ratio of 15-20:2-4; S4. Preparation of composite glass: 10-15 parts by weight of high aluminum borosilicate glass and 7-12 parts by weight of low-temperature lead-free glass were mixed and ball-milled to obtain a composite glass; S5. Preparation of glass protective lubricant for high-temperature alloys: Sodium acrylate and methyl methacrylate are added to water to prepare a monomer solution with a concentration of 25-30wt%, wherein the mass ratio of sodium acrylate to methyl methacrylate is 12-15:10-14, 7-10 parts by weight of the modified bentonite / silicon dioxide composite powder obtained in step S3 are added to 100 parts by weight of the monomer solution, and the mixture is stirred and mixed evenly, 0.5-1 parts by weight of an initiator is added, and the mixture is heated to 55-65°C and stirred for reaction for 3-5 hours, 25-30 parts by weight of the composite glass obtained in step S4, 3-5 parts by weight of carboxymethyl cellulose, and 4-6 parts by weight of boron nitride are added, and the mixture is ball-milled for 2-4 hours to obtain a glass protective lubricant for high-temperature alloys.
6. A glass protective lubricant for high temperature alloys obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the glass protection lubricant for high temperature alloys as claimed in claim 6 in the preparation of stainless steel forging.
Citation Information
Patent Citations
Surface protection lubricant for titanium alloy die forging process
CN102703183A
Glass protection lubricant powder used for titanium alloy die forging forming and paint
CN105132103A